Notice of the Remains of Two Ancient Lake Dwellings or Crannoges, in the Loch of the Clans, on the Estate of James Rose, of Kilravock, Nairnshire, with a Plan (Proceedings of the Society of Antiquaries of Scotland, 1864)
This article describes a cairn on a farm in Nairnshire. The hill the cairn was found on might once have been a crannog or islet in a loch. The author speculates that this may have originally been a crannog-like dwelling that was later re-purposed as a grave site, although he is not confident in his conclusions. Several piles of earth are also identified nearby, which the author suggests may be the remains of a second crannog.